Bioinspired strontium magnesium phosphate cement prepared utilizing the precursor method for bone tissue engineering - Liu, Qiaoyun; Liu, Changjiang; Wang, Weixing; Yuan, Liangjie; Wang, Yu; Yi, Xinzeyu; Pan, Zhenyu; Yu, Aixi (Frontiers in Bioengineering and Biotechnology, 2023)
Bioinspired strontium magnesium phosphate cements (SMPCs) for bone tissue engineering were prepared using a new, facile, environmentally friendly and high yielding (98.5%) precursor method. The bioinspired SMPCs have uniform particle distributions, excellent mechanical strengths and high biocompatibilities. The in vitro responses of bone marrow stromal cells to the SMPCs, including viability, osteogenic differentiation and alkaline phosphatase (ALP) activity, were evaluated. The results show that the SMPC containing 0.5 mol of strontium (referred to as SMPC-2) has a higher degradation rate and biological activity than magnesium phosphate cements and the other SMPCs. In addition, the synergistic effect of strontium and magnesium ion release from SMPC-2 creates a conducive environment for cell proliferation, mineralized calcium deposition and new bone formation. These observations demonstrate the feasibility of using the new precursor method to generate SMPCs and the utility of these biologically compatible and highly effective cements for bone tissue engineering.